Determinants and consequence of cost stickiness : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Accountancy at Massey University, Auckland, New Zealand - Costa, Mabel D (Massey University, 2020)
This research investigates the determinants and consequence of cost stickiness using data of publicly listed U.S. firms. Understanding the determinants of cost stickiness and its implications is extremely crucial, since it affects firms’ profitability, consequently, shareholders’ wealth. Moreover, cost management has even wider repercussions for both debt and equity investors in the areas of risk assessment and the trust of customers, employees, and other stakeholders in the community. Therefore, this study is organised into three different research essays: (i) financial constraint and cost stickiness; (ii) trade credit and cost stickiness; and (iii) cost stickiness and firm value. Essay One investigates the association between financial constraints and cost stickiness. Using a large U.S. sample from 1976 to 2016, I find that financially constrained firms exhibit less cost stickiness. I document that such low-cost stickiness supports both “good” and “bad” arguments depending on the managerial motivation, namely: earnings management incentives, agency problem and value-creating potential of SG&A costs. I also investigate whether the association between financial constraints and cost stickiness varies across the economic cycle. I find that low cost stickiness is observed during both economic expansion and economic contraction periods, although it is more pronounced during contraction. As resources drive the cost of a business, and financial constraints affect resource availability, studying cost behaviour of constrained firms makes a valuable contribution to the existing cost stickiness literature. In Essay Two, I examine the relation between trade credit and cost stickiness and further investigate the moderating effects of agency problem, product market competition, and customer concentration. I find that firms using high levels of trade credit exhibit lower cost stickiness and this is prevalent in the high agency problem sub-sample. In addition, in a non-competitive market, where the agency problem arises owing to lack of competition, trade credit plays an external monitoring role by attenuating cost stickiness. However, high customer concentration curtails this monitoring ability of trade credit providers. Finally, in Essay Three, I investigate the association between cost stickiness and firm value, and examine whether the association, if any, is mediated by cost of equity capital and cash flows. Using a large sample of U.S. data, I find a robust negative relationship between cost stickiness and firm value. I then explore whether resource adjustment, managerial expectations, and agency theories of cost stickiness affect the negative relation, and find some support for the agency view. Furthermore, I find evidence that the detrimental impact of cost stickiness on firm value is mediated partially through the cost of equity and cash flow channels. I enrich the cost management literature by integrating cost asymmetry with corporate finance.
Copyright is owned by the Author of the thesis. Permission is given for a copy to be downloaded by an individual for the purpose of research and private study only. The thesis may not be reproduced elsewhere without the permission of the Author.
Keywords: Cost; Business enterprises; United States; Costs; cost asymmetry; cost behaviour; financial constraint; trade credit; firm value; agency problem; resource adjustment; managerial expectation; 350103 Financial accounting